2016
DOI: 10.1148/radiol.2015151089
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Prostate Cancer: Quantitative Multiparametric MR Imaging Models Developed Using Registered Correlative Histopathology

Abstract: Purpose To develop multiparametric magnetic resonance imaging (mpMRI) models for generating a quantitative, user-independent, voxel-wise composite biomarker score (CBS) for prostate cancer (PCa) detection utilizing co-registered correlative histopathology and comparing CBS-based detection performance against single quantitative MRI (qMR) parameters. Materials and Methods After providing informed consent to participate in an IRB approved protocol, patients with an initial diagnosis of PCa electing surgery as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 33 publications
1
68
0
Order By: Relevance
“…62 ADC values, which should be independent of field strength, also appear to be larger than expected compared to quantitative studies reported at 3T. 63 However, for all parameters, the acquisition-, subject-, and field-dependent variability cannot be adequately assessed until more extensive targeted evaluations are performed.…”
Section: Discussionmentioning
confidence: 76%
“…62 ADC values, which should be independent of field strength, also appear to be larger than expected compared to quantitative studies reported at 3T. 63 However, for all parameters, the acquisition-, subject-, and field-dependent variability cannot be adequately assessed until more extensive targeted evaluations are performed.…”
Section: Discussionmentioning
confidence: 76%
“…However, its interpretation remains difficult and multiparametric MR imaging is characterized by substantial interreader variability (3-6), which limits its broad acceptance. Computer-aided diagnosis (CAD) systems combining various image features have shown promising results in characterizing prostate tissues (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). However, the intensity and texture of MR images depend on the manufacturer and settings of the MR imager.…”
Section: Training Populationmentioning
confidence: 99%
“…DW-MRI has been demonstrated to be the most important component of mp-MRI compared to T2W-MRI and DCE-MRI due to its high sensitivity to microstructural changes related to cancer [5], [6]. However, mp-MRI studies use DW-MRI in its simplest form by deriving the ADC map.…”
Section: Introductionmentioning
confidence: 99%